Future Development of Medical Informatics from the Viewpoint of Health Telematics - Pfeiffer, K. P. (Methods of Information in Medicine, 2009)
Objectives: The transformation process of the health care systems in most countries in direction of integrated care needs the support of information and communication technology. The central element of this development is the electronic health care record. But there are many other applications around this record and the functionality and usability of these systems has to be improved and extended.Methods: A system-analytic approach to integrated care is used to analyze the possibilities and the role of information and communication technology in current and future health and social care systems.Results: The key elements of the improvements in the next years are the integration of evidence-based knowledge in the care process, the improvement of the usability for patients and health care providers, the development of pro-active systems for decision support, the support of the mobility of patients and the activities of daily living, the integration of data form molecular biology, semantic interoperability and last but not least the processing and analysis of these data. In a series of tables requirements of the functionality of eHealth applications are summarized.Conclusion: Research in medical informatics has to focus on strategic concepts and how to transform the demands of a modern integrated health and social care system into user-friendly, secure and efficient ICT solutions and to support the citizen’s responsibility for her/his own healthcare. But there is also a high demand for research to improve the technology of ICT systems in health and social care.
Keywords: Integrated care; decision support; eHealth; electronic patient record; usability; knowledge management